Romans disarmed resisting empire, demanding justice - Keesmaat, Sylvia C.; Walsh, Brian J. 1953- (Grand Rapids, Michigan Brazos Press, 2019)
Reading Romans and disarming empire -- Kitchen walls and tenement halls: hearing Romans -- Empire and broken worldviews -- Homeless in Rome -- Land, ecology, and the defilement of home -- Economic justice and the kingdom of life -- Welcoming the powerless -- The Pax Romana and the gospel of peace -- Romans, sexuality, and empire -- Salvation, lament, and hope
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc